Brazing of Porous Copper Foam with Copper Sheet Using CuNiSnP Amorphous Filler Metal - Mookam, Niwat; Jattakul, Prajak; Rakphet, Tipsuda; Kanlayasiri, Kannachai (My University, 2021)
This research studies effects of the brazing time on interfacial microstructure of brazed joint between the porous copper foam (PCF) and Cu substrate using CuNiSnP amorphous filler metal. To examine the interfacial microstructure and its properties, an assessment of PCF/CuNiSnP/Cu brazed joints was conducted after electric furnace brazing under hydrogen (H2) atmosphere. The results showed that the interfacial microstructure was thick for short brazing time specimens and thin for prolonged brazing time specimens. The interfacial microstructures consisted of Cu-rich solid solution, (Cu, Ni)3P, and Cu3P as a eutectic structure discovered in the brazing region at different brazing times of 5, 10, and 20 min. Only the Cu-rich solid solution and (Cu, Ni)3P were found in the specimen with brazing time of 30 min. indicating that different brazing times affected interfacial microstructures and therefore reliability of the brazed joints.
Keywords: Amorphous Filler Metal; Brazing; Interfacial; Microstructure; Porous Copper foam